Sex Steroids, Adult Neurogenesis, and Inflammation in CNS Homeostasis, Degeneration, and Repair - Larson, Tracy A. (Frontiers in Endocrinology, 2018)
Sex steroidal hormones coordinate the development and maintenance of tissue architecture in many organs including the central nervous systems (CNS). Within the CNS sex steroids regulate the morphology, physiology, and behavior of a wide variety of neural cells including, but not limited to, neurons, glia, endothelial cells, and immune cells. Sex steroids spatially and temporally control distinct molecular networks, that, in turn modulate neural activity, synaptic plasticity, growth factor expression and function, nutrient exchange, cellular proliferation, and apoptosis. Over the last several decades it has become increasingly evident that sex steroids, often in conjunction with neuroinflammation, have profound impact on the occurrence and severity of neuropsychiatric and neurodegenerative disorders. Here I review the foundational discoveries that established the regulatory role of sex steroids in the CNS and highlight recent advances towards elucidating the complex interaction between sex steroids, neuroinflammation, and CNS regeneration through adult neurogenesis. The majority of recent work has focused on neuroinflammatory responses following acute physical damage, chronic degeneration, or pharmacological insult. Few studies directly assess the role of immune cells in regulating adult neurogenesis under healthy, homeostatic conditions. As such, I also introduce tractable, non-traditional models for examining the role of neuroimmune cells in natural neuronal turnover, seasonal plasticity of neural circuits, and extreme CNS regeneration.